Enterprise systems education in the 21st century - Targowski, Andrzej; Tarn, J. Michael; 1960- (Gale virtual reference library)
This book presents methods of reengineering business curricula in order to use ES solutions. It also helps ES vendors understand the higher education environment so they can support college and university programs--Provided by publisher.